Pengaruh Model Pembelajaran Inkuiri Terbimbing Berbantuan LKS Terhadap Kemampuan Berpikir Kritis Siswa Kelas X SMAK Setia Bakti Ruteng - Rosalia Mulyani (STIKes Ibnu Sina Ajibarang, 2023)
This study aims to determine the effeck of the guided iquiry learning model assisted by LKS on student’s critical thinking skills. This research subjects were students of class X IIS 2 dan X IIS 4. The result of the halp of SPSS for windows thorough the Mann Whiney test. The results of the hypothesis test show that thevalue of sig (2 table) is < 0,05 so that H0 is rejected and H1 is accepted. This mean that there is an influence of the guided inquiry learning model assisted by LKS on the by critical thinking skills of X IIS students at SMAK Setia Bakti Ruteng the N-gain result for the eksperimental clas is 0,80 with the high category while the control class is 0,70 with the medium category. This shows thet there is an influence with the guided inquiry learning model assisted by LKS.